(untitled) (Revista Brasileira Multidisciplinar, 2019)
Vehicles of public transport present surfaces that receive high index from manual contact being able to act as potential reservoirs of pathogens. The present study evaluated the bacterial contamination in vehicles of the intercampi transport of a federal university in the city of Uberlândia, Minas Gerais. For this, samples of four buses had been collected, in four strategical places of bigger contact with the hands of the users, in total of 192 samples, analyzed how much the counting of bacteria mesophilic, qualitative analysis and the profile of resistance to antimicrobial. The count of bacteria had been bigger in the bar of entrance and horizontal upper bar, and the identified bacteria more had been: Enterobacter cloacae, Serratia marcescens, Salmonella sp., Shigella sp. e Staphylococcus aureus, with resistance mainly to the ampicillin, aztreonam, imipenem, for the enterobacterias and penicillin and erythromycin for the S. aureus. The results of this study suggest that the contamination of the evaluated vehicles reflects the hands of the users, therefore, it is also necessary to adopt policies of good hygiene practices.